Re-thinking the cost of supply chain security - Haelterman, Harald (Crime, law and social change, 2011)
Post 9/11 we have witnessed the introduction and further strengthening of a range of trans-border security programs designed to protect international supply chains against acts of unlawful interference. In some cases compliance with these programs is mandatory. In other cases compliance results in a preferential treatment by appropriate authorities. To a great extent, these programs comprehend the introduction of situational measures. In most instances, however, operators within the supply chain - being made responsible for their actual implementation - are left with limited guidance. In this paper it is argued that a lack of guidance may result in measures being introduced without taking full account of their potential consequences. Based on an analysis of previous research findings and on the outcome of a literature review, direct and indirect implementation costs have been differentiated from a range of (consequential costs provoked by) potential reverse effects, and from a series of generic preconditions, enabling practitioners in industry to conduct a proper cost analysis and come to an informed decision on what particular measure(s) best to implement. It is argued that criminology and management science can support this decision making process, provided that policy makers allow operators a certain freedom of choice between alternative measures and approaches.